2017
DOI: 10.1017/inp.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Using Microwave Soil Heating to Inhibit Invasive Species Seed Germination

Abstract: Successful invasive plant eradication is rare, because the methods used target the adult stage, not taking into account the development capacity of a large seedbank. Heating by microwave was considered, because it offers a means to quickly reach the temperature required for loss of seed viability and inhibition of germination. Previous results were not encouraging, because homogeneous and deep-wave penetration was not achieved, and the various parameters that can affect treatment effectiveness were incompletel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…The effects of 915‐MHz microwave treatment of a soil to eradicate the seed bank of invasive species were investigated under four radiation conditions that combined power level and exposure time. The effectiveness of the four conditions chosen according to De Wilde et al (), related to the rates of seed germination of three invasive plant species, was confirmed here on Festuca rubra seed germination. More precisely, the 2 kW‐8 and 4 kW‐4 min conditions caused soil temperature to reach at least 80°C, leading to complete inhibition of Festuca seed germination, and were designated effective treatments.…”
Section: Discussionsupporting
confidence: 74%
“…The effects of 915‐MHz microwave treatment of a soil to eradicate the seed bank of invasive species were investigated under four radiation conditions that combined power level and exposure time. The effectiveness of the four conditions chosen according to De Wilde et al (), related to the rates of seed germination of three invasive plant species, was confirmed here on Festuca rubra seed germination. More precisely, the 2 kW‐8 and 4 kW‐4 min conditions caused soil temperature to reach at least 80°C, leading to complete inhibition of Festuca seed germination, and were designated effective treatments.…”
Section: Discussionsupporting
confidence: 74%
“…Seed susceptibility to microwave treatment is mainly attributed to the direct effect of heat transfer from the surrounding soil (Nelson ) and is entirely temperature‐dependent (Barker & Craker ). Studies have shown that soil microwave treatment can kill seeds of several species in the soil (Davis et al ; Barker & Craker ; Brodie et al ; De Wilde et al ). In our experiment, the drastic reduction of seedling emergences from a seed bank exposed to certain treatments confirms the effectiveness of soil microwave treatment in inhibiting the seedling emergence of a wide diversity of species (here, at least 31 species).…”
Section: Discussionmentioning
confidence: 99%
“…Soil microwave treatment could therefore decrease invasive species seedling emergence through a direct effect of heat on seeds, and in a second step, through modifications of soil properties and functioning. In the study of De Wilde et al (), heating effects on soil properties and biota could not be assessed because seedling emergence was not performed on treated soil. In the present study, the significant decrease in D. stramonium and S. gigantea percentages of seedling emergence after soil exposure to the 2kW4min and 4kW4min treatments is surprising, as the longest and highly effective treatment, 2kW8min, had no impact compared with the control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations